2024
DOI: 10.1038/s41467-024-48301-5
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-glucans from bacterial necromass indicate an intra-population loop within the marine carbon cycle

Irena Beidler,
Nicola Steinke,
Tim Schulze
et al.

Abstract: Phytoplankton blooms provoke bacterioplankton blooms, from which bacterial biomass (necromass) is released via increased zooplankton grazing and viral lysis. While bacterial consumption of algal biomass during blooms is well-studied, little is known about the concurrent recycling of these substantial amounts of bacterial necromass. We demonstrate that bacterial biomass, such as bacterial alpha-glucan storage polysaccharides, generated from the consumption of algal organic matter, is reused and thus itself a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…Fourth, a recent study from the Helgoland time series showed that bacteria not only expressed polysaccharide utilization loci for utilization of beta-glucans (produced by phytoplankton), but also for alpha-glucans (produced by bacteria), and the authors hypothesized that a recycling of bacterial glucans occurs [ 41 ]. This hypothesis was corroborated by follow-up results in the same time series showing that the phytoplankton storage polysaccharide laminarin fuels the synthesis of alpha-glucans in bacteria during phytoplankton blooms, and that these are used as a carbon source by other bacteria if liberated by cell lysis ([ 42 ], also see the SI for overlaps in the suggested taxonomy of important taxa between this and our study). The authors of that study conclude that large amounts of carbon may get redirected via an intrapopulation loop, which corroborates the outcomes of our mechanistic inference approach by metatranscriptomic analyses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Fourth, a recent study from the Helgoland time series showed that bacteria not only expressed polysaccharide utilization loci for utilization of beta-glucans (produced by phytoplankton), but also for alpha-glucans (produced by bacteria), and the authors hypothesized that a recycling of bacterial glucans occurs [ 41 ]. This hypothesis was corroborated by follow-up results in the same time series showing that the phytoplankton storage polysaccharide laminarin fuels the synthesis of alpha-glucans in bacteria during phytoplankton blooms, and that these are used as a carbon source by other bacteria if liberated by cell lysis ([ 42 ], also see the SI for overlaps in the suggested taxonomy of important taxa between this and our study). The authors of that study conclude that large amounts of carbon may get redirected via an intrapopulation loop, which corroborates the outcomes of our mechanistic inference approach by metatranscriptomic analyses.…”
Section: Discussionsupporting
confidence: 85%
“…al. [ 42 ] suggests that the proposed internal recycling also takes place at other places in significant amounts, and we encourage future analyses of aquatic microbial communities to also resolve fluxes between heterotrophic prokaryotes. The assumption applied thus far that heterotrophic prokaryotes only consume DOM and do not also produce it for further consumption by others may be a gross oversimplification.…”
Section: Discussionmentioning
confidence: 93%